PENGARUH SIKAP DAN MOTIVASI SISWA TERHADAP HASIL BELAJAR MATEMATIKA - Zuari Anzar; Heri Retnawati (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2022)
Students' attitudes are less positive towards mathematics and students' motivation to learn is also still lacking in learning mathematics. This study aims to determine the influence of students' attitudes and motivation together on the results of mathematics learning for class VIII of SMP in Baubau. This research is an ex post facto study with the population is all students of class VIII in one of SMP in Baubau which consists of 10 parallel classes with 304 students. Based on this population a sample of 47% or 142 people ware taken. 142 samples were taken from 10 classes. Thus, each class is taken at random as much as 47% of the total number of students in each class with a proportional random sampling technique. Based on the results of multiple linear regression analysis of students' attitudes towards mathematics (X1) and students' motivation in mathematics (X2) together with students' mathematics learning outcomes (Y) it was found that the average score of students' mathematics learning outcomes (Y) will experience changes of 0.689 for each unit of change that occurs in students' attitude scores in mathematics (X1) and is also expected to experience a change of value of 0.190 for each unit that occurs in students' motivation test scores (X2). It was concluded that the attitudes and motivation of students in mathematics had a significant positive effect on mathematics learning outcomes of students in one of SMP in Baubau.